THE ROLE OF THE LITERARY CRITIC: STUDY OF THE OBJECT AND AESTHETICS IN THE PROCESS OF SEMIOTICS THROUGH A CRITICAL READING - Mantovano, Luiz Carlos Moreira Ramo; de Oliveira, Custódia Annunziata Spenciere; Ferreira, Elizete Albina (Seven Editora, 2024)
The respective essay aims to guide students of Literary Criticism and Comparative Aesthetics through the study of the Work and criticism (2019, p 9-31) and Aesthetics and Semiotics (2019, p 1-8) of Literature and Intersemiotic Systems, by Flávio Khote. From this perspective, the analysis of the role of the critic will be a relevant theme in this essay, in addition to enunciations in relation to the role of semiotics within literature and the study of the object among the aesthetics in comparison. Therefore, comparative studies will be used with the semiotic theory of Algirdas Julien Greimas, For Greimas, the sign is called "textual aspect", Semiotics is the theory of signification and its object is not the sign, but the Semiotic Systems. According to Greimas, "each science has its particular semiotics". This comparative study seeks to substantiate the role of the critic and assist him in his training, guiding him not to fall into traps preformed by methodological procedures of the criticism of comradeship, in this way, it seeks to form critics who excel in the ethical and isonomic precepts of literary criticism. DOI:https://doi.org/10.56238/sevened2024.031-039